On closed finite gap curves in spaceforms II. Issue 1 (6th May 2020) - Klein, Sebastian; Kilian, Martin
Abstract: We prove that the set of closed finite gap curves in hyperbolic 3-space H^3 is W^2, 2 -dense in the Sobolev space of all closed W^2, 2 -curves in H^3 . We also show that the set of closed finite gap curves in any two-dimensional space form E^2 is W^2, 2 -dense in the Sobolev space of all closed W^2, 2 -curves in E^2 .